Thermal Hazards of Synthesizing a Grignard Reagent under Different Dosing Rates - Wei Wang; Jiancun Gao; Chenguang Shi; Shengnan Wang; Yujing Li; Xiong Dai; Tianmeng Jiang (International Journal of Chemical Engineering)
Thermal safety during the synthesis of a Grignard reagent under different dosing rates was evaluated in this work. A reaction calorimeter (SIMULAR) was used to investigate the heat release under isothermal experiment in the range of 0.5–2.0 g⋅min−1 dosing rates. The thermal decomposition of the Grignard reagent was analyzed using accelerating rate calorimetry (ARC). Furthermore, the risk assessment of thermal runaway was analyzed using a risk matrix and a Stoessel criticality diagram. The results indicate that decreasing the dosing rate can decrease the risk level of synthesizing the Grignard reagent from class 3 to class 1. However, the risk level was class 3 at different dosing rates when the induction period was considered. In the case of cooling failure, the most hazardous moment was the induction period, followed by the dosing period. These findings provide further evidence that the dose rate of 0.5 g⋅min−1 was safer to produce Grignard reagents.